The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.7759/cureus.26180
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic Control for Type 2 Diabetes Mellitus Patients: A Systematic Review

Abstract: Diabetes mellitus is a chronic metabolic disorder resulting in hyperglycemia and microvascular and macrovascular complications in individuals globally. Type 2 diabetes mellitus (T2DM) is highly prevalent and accounts for 90% of patients. Maintaining blood glucose concentration is essential to avoid severe complications.Glycemic control is the optimal serum glucose concentration in diabetic patients. It is necessary to identify factors affecting the glycemic control of patients to prevent control and complicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 29 publications
0
25
0
Order By: Relevance
“…We will evaluate the impact of the interventions on any of the following outcomes: Good glycemic control. Defined by the American college of endocrinologists as glycated hemoglobin (HbA1c %) levels below 7% or fasting blood sugar levels below 110mg/dl (6.1 mmol/l)(4). Diabetes awareness.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We will evaluate the impact of the interventions on any of the following outcomes: Good glycemic control. Defined by the American college of endocrinologists as glycated hemoglobin (HbA1c %) levels below 7% or fasting blood sugar levels below 110mg/dl (6.1 mmol/l)(4). Diabetes awareness.…”
Section: Methodsmentioning
confidence: 99%
“…Good glycemic control. Defined by the American college of endocrinologists as glycated hemoglobin (HbA1c %) levels below 7% or fasting blood sugar levels below 110mg/dl (6.1 mmol/l)(4).…”
Section: Methodsmentioning
confidence: 99%
“…Clinical factors, medication-related factors and behavioural factors also play crucial roles in determining glycaemic control, highlighting the complex interplay of factors that influence diabetes management outcomes. 28 A correlated study pooled odds ratio for lower extremity amputation (LEA) and reported 2.04 (95% CI: 0.91-4.57) in cohort studies comparing A1C >7.0%-7.5% versus lower A1C levels and 4.80 (95% CI: 2.80-8.13) in studies comparing A1C 8% versus 8%. Results indicated that A1C levels 8% and fasting glucose levels 126 mg/dL are associated with an increased risk of LEA in patients with DFUs.…”
Section: Glycaemic Controls In Diabetic Foot Patientsmentioning
confidence: 99%
“…Therefore, good glycaemic control in diabetics is essential to reduce the risk of these acute and chronic conditions. 1–3 This is generally achieved by self-monitoring of blood glucose levels which is predominantly conducted using electrochemical biosensors. These devices can either be enzymatic or non-enzymatic and typically employ amperometric detection.…”
Section: Introductionmentioning
confidence: 99%